Challenge or hindrance: Does job stress affect presenteeism among Chinese healthcare workers? - Yang, Tianan (J Occup Health, 2017)
BACKGROUND: We examined the effects of challenge stress and hindrance stress on general health and presenteeism among Chinese healthcare workers. METHODS: Structural equation modeling was used to evaluate data from a national hospital survey in China (n = 1392). Job stress, general health, and presenteeism were measured by the Perceived Ability to Work Scale, the 8-item Short-Form Health Survey, and the Challenge- and Hindrance-Related Self-reported Stress Scale. RESULTS: Challenge stress and hindrance stress were significantly positively correlated (β = 0.62, SE = 0.021; p < 0.001). Challenge stress was directly negatively associated with presenteeism (β = -0.05, SE = 0.037; p < 0.001), while hindrance stress was positively associated with presenteeism (β = 0.25, SE = 0.040; p < 0.001). These associations with presenteeism were partially mediated by health. CONCLUSIONS: Hospital managers should provide healthcare workers with an appropriate level of challenge, but employee health is the most important consideration. Further efforts targeting job stress and health of junior healthcare workers are required.